1992
DOI: 10.1109/3.119536
|View full text |Cite
|
Sign up to set email alerts
|

Transparent boundary condition for the beam propagation method

Abstract: A new boundary condition algorithm is presented that passes outgoing radiation freely with a minimum reflection coefficient (typically 10-5) while inhibiting the flux of incoming radiation. In contrast to the commonly used absorber method, this algorithm contains no adjustable parameters and is thus problem independent. It adapts naturally to a standard Crank-Nicholson difference scheme and is shown to be accurate and robust for both twoand three-dimensional problems.The beam-propagation method is currently th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
93
0
12

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(105 citation statements)
references
References 9 publications
0
93
0
12
Order By: Relevance
“…Here is the difference between the core and cladding radii , and is similar to (16) but with replaced by the peak spatial frequency from the modal Fourier expansion (14), which is zero for even LP modes, but nonzero for odd. The extremities in the bend loss correspond to the conditions (22) where (23) Furthermore, these oscillations disappear for large bend radii, , such that the caustic boundary lies outside of the fiber cladding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here is the difference between the core and cladding radii , and is similar to (16) but with replaced by the peak spatial frequency from the modal Fourier expansion (14), which is zero for even LP modes, but nonzero for odd. The extremities in the bend loss correspond to the conditions (22) where (23) Furthermore, these oscillations disappear for large bend radii, , such that the caustic boundary lies outside of the fiber cladding.…”
Section: Discussionmentioning
confidence: 99%
“…Of the various BPM versions available, a semi-vectorial variation was used in this paper, as described in [13]. At the simulation boundaries, transparent boundary conditions were used to minimize unwanted reflections [14].…”
Section: Bent Fiber Simulationmentioning
confidence: 99%
“…The CGO solution for GB wave field (27) completely coincides with the results of quasi-optical theory of diffraction [10][11][12]. The eikonal-based CGO equations for complex phase front curvature (15) and amplitude (19) are ordinary differential equations and can be easily solved numerically by the Runge-Kutta method for arbitrary inhomogeneous waveguides. To assess accuracy of the numerical CGO algorithm, we have compared CGO numerical results for GB width, phase front curvature and amplitude with analytical solutions (27-29) and obtained comparatively high accuracy.…”
Section: Gaussian Beam Diffraction In Inhomogeneous Planar Waveguide mentioning
confidence: 84%
“…Taking into account the loss between the fiber laser and waveguide, a Gaussian field is chosen as the initial field. In addition, the transparent boundary condition (TBC) (Hadley 1992a) was used in order to prevent spurious reflection from the computational window edges. The results showed that the configurations of t < 5.8 mm and w ¼ 6 mm will have a single-mode transmission.…”
Section: The Design Of Single-mode Waveguidesmentioning
confidence: 99%